Dark Web: The Uniluminated Side of the World Wide Web - Nath, Asoke; Mondal, Romita (International Journal of Computer Sciences and Engineering, 2019)
The Dark Web is a part of the World Wide Web that exists on dark-net whose content is intentionally hidden, and cannot be accessed using normal search engines and require some specific browsers such as Tor browser. Dark web uses network such as Tor, I2P.While tor provides anonymity of users and make them untraceable, I2P provides anonymous hosting of websites. As the dark web hides the user’s identity and maintains secrecy, it can be used for legitimate purpose as well as illicit purpose. From smuggling of drugs and weapons to other illicit items, from hacking other’s information to using those for forging, from counterfeiting money to using crypto currency, dark web can play a number of roles in malicious activity. On the other hand, government and legitimate authority use dark web for military application such as online surveillance, sting operation and to track the malicious activities. This paper describes dark web emphasizing on how it is accessed, how the tor network (onion routing) and I2P work to hide user’s identity, how one can use TOR to access dark web, recent technological development, details on usage of dark web i.e. how different malicious activities are done using dark web, how the terrorist groups are using darkweb, how the legitimate authorities are using dark web to unveil some user’s identity and to stop the illicit activities and the future scope of dark web.